Cytologic Diagnosis of Oncocytic Neoplasms of the Thyroid Gland: The Importance of the Clinical Scenario. Issue 10 (November 2019) - Straccia, Patrizia; Santeusanio, Giuseppe; Pierconti, Francesco; Brunelli, Chiara; Fadda, Guido
Abstract : It is a diagnostic challenge to differentiate benign and malignant thyroid neoplasms made up of Hürthle (or oncocytic) cells on cytologic material. They are large, polygonal cells with marked eosinophilic, granular cytoplasm reflective of overly abundant mitochondria. These cells commonly occur in nodular goiters and dominant adenomatous or hyperplastic nodules though they may also be the predominant component of neoplastic lesions. There are significant controversies concerning the optimal management of patients with oncocytic cell carcinoma. This review provides an overview of the most significant studies addressing the distinction between benign and malignant Hürthle cell lesions on cytology and histology.